Sytuacja osób młodych na rynku pracy w województwie śląskim w latach 2011–2016 - Oziębłowski, Bartosz (Wydawnictwo Uniwersytetu Rzeszowskiego, 2018)
The key objective of the study is to depict unemployment among young people in the provice Silesia in 2011–2016. As a thesis, it was assumed that in recent years unemployment among people who enter the labor market is falling. On the basis of analyzes of industry materials, this thesis has been proved. At the same time, we can talk about a slower decline in the level of unemployment among university graduates, rather than considering the total number of unemployed people.
Keywords: labor market; unemployment; young; graduates of high schools